On the improvement of thermal comfort of university students by using electrically and chemically heated clothing in a cold classroom environment. (December 2015) - Song, Wenfang; Wang, Faming; Zhang, Chengjiao; Lai, Dandan
Abstract: This study aimed to examine the effectiveness of two types of heated clothing (i.e., electrically and chemically heated clothing) in improving thermal comfort of university students while sitting in a simulated cold classroom environment. Eight male subjects performed three 90-min trials and three test scenarios were selected: EHC (i.e., electrically heated clothing), CHC (i.e., chemically heated clothing) and CON (i.e., the control, no heating). The trials were conducted in a climate chamber where the air temperature was 8.0 °C, RH = 80% and the air velocity was 0.17 m/s. Significantly higher mean skin (in both EHC and CHC) and body temperatures (in CHC) were found in the heated clothing compared to CON throughout the entire trials ( p  < 0.05). The whole-, upper- and lower-body thermal (TS) and comfort sensations (CS) were improved in the heated clothing (rated 'Neutral' and 'Comfortable', respectively, throughout the test) than CON (aggravated with time) ( p  < 0.05). Significantly higher finger temperatures (the 65–90th min, p  < 0.05), finger blood flow (the 2–5th min in EHC and the 2–10th min in CHC, p  < 0.05) and remarkably improved TSs at the hands and feet were detected in EHC and CHC than CON ( p  < 0.05). Finger dexterity was improved in CHC at the end of the test than the beginning ( p  < 0.05). CHC offered more heating benefits than EHC in terms of local skin temperature elevation at the trunk ( p  < 0.05). In summary, the heated clothing could serve as an effective method to improve both local- and whole-body thermal comfort of university students while sitting in cold classrooms. Highlights: Two types of heated clothing (i.e., electrically heated clothing and chemically heated clothing) were designed. The performance of EHC and CHC in improving thermal comfort of university students in a cold environment was examined. Both EHC and CHC could effectively improve the local and whole body thermal comfort. Student performance, i.e., finger dexterity, was improved in CHC within the 90-min exposure.